INVENTARISASI POTENSI WISATA BUDAYA DI PANTAI SUWUK KECAMATAN PURING KABUPATEN KEBUMEN - sri nani hari yanti (Faculty of Humanities, Universitas Jenderal Soedirman, 2016)
Beach Name Suwuk not too familiar. In Fact, the beauty of coastal landscape in Sub croton this Kebumen District wxtraordinary charming. In addition to its beauful beaches, the surrounding area is a mix bed of the sea, cluster karst hills, coconut plantations and paddy fields. The potential that the Government attempted District Kebumen to explore the region’s financial resources. Yutuk and Hadroh are culturals potential of the existing Suwuk Beach Village Tambakmulyo as main attraction besides the natural beauty of the beach. Seeing the opportunity, the potential cultural of Yutuk and Hadroh needs to be developed. Innovations necessary for this potential is not monotonous. So the beach could be a target Suwuk Tourism mainstay Kebumen District